The effect of inhomogeneities in particle distribution on the dielectric properties of composite films - Starke, T; Johnston, C; Hill, S; Dobson, P; Grant, P (2006)
A practical approach for the modelling of the dielectric constants of thin composite films is presented. A general distribution function for composition fluctuations in the thin composite films is introduced to describe the transition from a non-percolative to a percolative morphology using physically meaningful parameters and is applied to model a wide range of experimental and simulated polymer-ceramic composite film behaviour from the literature, up to ceramic particle filler volume fractions of 75%. The parameters describing the morphologies of the various composites are used to predict effective dielectric properties with good accuracy. The model is applied further to composites that show early percolation behaviour, and the deviation of their effective dielectric behaviour from the standard effective medium theory at high filler volume fractions is discussed. © 2006 IOP Publishing Ltd.